EKSPERIMENTASI MODEL PEMBELAJARAN THINK TALK WRITE (TTW) DENGAN PENDEKATAN MATEMATIKA REALISTIK (PMR) TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KEMAMPUAN PENALARAN MATEMATIKA DAN KREATIVITAS BELAJAR SISWA SMP SE-KABUPATEN WONOGIRI - Utami, Novia Fajar; Budiyono, Budiyono; Usodo, Budi (Jurnal Pembelajaran Matematika, 2014)
Abstract: This aims of the research were to determine: (1) which one that give better achievement, learning with TTW with RMA, TTW, or conventional, (2) which one that give better achievement, the students having high, medium, or low mathematics reasoning ability, (3) which one that give better achievement, the students having high, medium, or low creativity, (4) in each learning model, which one category of mathematics reasoning ability that give better achievement, the students having high, medium, or low mathematics reasoning ability, (5) in each learning model, which one that give better achievement, the students having high, medium, or low creativity, (6) in each category of mathematics reasoning ability, which one that give better achievement, the students having high, medium, or low creativity, (7) in each learning model for each category of mathematics reasoning ability, which one that give better achievement better, the students having high, medium, or low creativity. Prior knowledge data are examined by using one-way ANOVA with unbalanced cells. It shows that three classes have balance prior knowledge. Meanwhile, the technique of analyzing the data was three-ways ANOVA with unbalanced cells. The result of research showed that: (1) TTW with RMA provided better achievement than TTW and conventional, and also TTW provided better achievement than conventional, (2) the students having high and medium mathematics reasoning ability had same achievement, and also than the students having high and medium mathematics reasoning ability had better achievement than those having low mathematics reasoning ability, (3) the students having high, medium, and low creativity had the same achievement, (4) in each learning model, the students having high and medium reasoning ability had the same achievement, and also than the students having high and medium mathematics reasoning ability had better achievement than those having low mathematics reasoning ability, (5) in each learning model, the students having high, medium, and low creativity had the same achievement, (6) in each category of mathematics reasoning ability, the students having high, medium, and low creativity had the same achievement, (7) in each learning model for each category of mathematics reasoning ability, the students having high, medium, and low creativity had the same achievement.Keywords: Think Talk Write (TTW), Realistic Mathematics Approach (RMA), mathematics reasoning ability, learning creativity, mathematics achievement.